PROFILE OF STUDENTS' SPATIAL ABILITY IN SOLVING GEOMETRY PROBLEMS IN TERMS OF DAVID KEIRSEY'S PERSONALITY TYPES - Shofilah, Dita Ayu; Susanto, Susanto; Suwito, Abi; Sunardi, Sunardi; Monalisa, Lioni Anka (Kadikma, 2021)
This study aims to describe the ability of spatial geometry of class XI MIPA 1 SMA Negeri 2 Jember in terms of David Keirsey's personality type. Spatial ability in this study is the ability to understand the world of space based on elements of spatial abilities which include: spatial perception, mental rotation, and spatial visualization. This type of research is a descriptive study with a qualitative approach. The data collection method in this research is questionnaire, spatial test, and interview. Then, based on the results of the test and interview analysis, it was found that the Guardian students could fulfill all spatial indicators. Artisan students in imagining and rotating spaces can think quickly and answer questions correctly, compared to guardian and idealistic students. Idealistic students in the ability to see the surface of the unit cubic structure more than the point of view (from the front, right side, and top) cannot describe it precisely. Meanwhile, rational students on the mental rotation element for the first indicator are still unable to rotate a spatial shape and can imagine the rotation or rotation of a spatial shape accurately.